Occurrence and distribution of dissolved tellurium in Changjiang River estuary - 吴晓丹 宋金明 李学刚 (Chinese journal of oceanology and limnology, 2014)
With the implementation of the GEOTRACES program, the biogeochemical cycle and distribution of tellurium (Te) in marine environments are becoming increasing environmental concerns. In this study, the concentration of dissolved Te in the Changjiang (Yangtze) River estuary and nearby waters was determined in May 2009 by hydride-generation atomic fluorescence spectrometry to elucidate the abundance, dominant species, distribution, and relationship with environmental factors. Results show that: (1) dissolved Te was low owing to its low abundance in the Earth’s crust, high insolubility in water, and strong affinity to particulate matter; (2) Te(IV) and Te(VI) predominated in surface water. Te(VI) was the dominant species in bottom water, and Te(IV) was the minor species; (3) Horizontally, resulting from low phytoplankton metabolism and the weak reduction from Te(VI) to Te(IV) in the shore, Te(IV) was concentrated in the central zone instead of the coastal region. However, Te(VI) was abundant near the mouth of the Changjiang River where the Changjiang water is diluted and in the area to the south where the Taiwan Warm Current invaded. In the adsorption-desorption process, Te(IV) was negatively related to suspended particulate matter (SPM), indicating that it was adsorbed by particulate matter. While for Te(VI), the positive correlation with SPM suggested that it was desorbed from the solid phase. In the estuary, dissolved Te had a negative correlation to salinity. However, it deviated from the dilution line in high-salinity regions due to the invasion of the Taiwan Warm Current and the mineralization of organic matter. The relationship between Te(IV) and SPM nutrients indicated that it was more bioavailable and more related to phosphorus than to nitrogen. Progress in the field is slow and more research is needed to quantify the input of Te to the estuary and evaluate the biochemical role of organisms.